Evaluation of Prognostic Nutritional Index and Sarcopenia in Polycythemia Vera and Essential Thrombocythemia - Öztürk, Erman; Gönen, Özlem; Erbakan, Ayşe; Erdoğan Özünal, Işıl (Cerrahpaşa Medical Journal, 2021)
Objective: Sarcopenia is defined as a loss of skeletal muscle mass and function and is known to be a prognostic factor for patients diagnosed with cancer. Prognostic nutritional index (PNI), in addition to sarcopenia; is an indicator of immune status, inflammation, and nutrition. Catabolic process and transformation to myelofibrosis (MF) due to the increase of inflammatory cytokines may develop in myeloproliferative neoplasias (MPN) such as polycythemia vera (PV) and essential thrombocythemia (ET). In this study, we aimed to evaluate the nutritional status in patients with PV and ET by anthropometric measurements and to compare muscle strength and PNI scores with a control group. Methods: Anthropometric measurements were performed on 44 patients with PV and ET, who did not develop MF, and 35 healthy individuals without a history of diagnosis of cancer, as a control group. Fat mass (FM), muscle mass (MM), and fat-free mass (FFM) were evaluated by bioelectrical impedance analysis (BIA). Muscle strength was measured with a hand dynamometer. Results: There was no difference between the patient and the control groups in terms of age, sex, and body mass index. There was no significant difference between the measurements of FM, MM, and FFM in both groups. The PNI score was 55.9 (SD ± 3.5) in the patient group and 57.6 (SD ± 4.3) in the control group (P = .17). The mean of muscular strength in women was 14.3 (SD ± 4.5) kg in the patient group and 14.7 (SD ± 3.7) kg (P = .5) in the control group; and the mean of muscular strength in men was 32.6 (SD ± 7) kg in the patient group and 30 (SD ± 4.7) kg in the control group (P = .51). Conclusion: Polycythemia vera and ET are neoplastic diseases characterized by an increase in the inflammatory cytokines. In our study, it was determined that these patients had similar muscle mass, muscle strength, and PNI score compared to individuals without a diagnosis of cancer. These findings revealed that patients diagnosed with MPNs such as PV and ET do not develop sarcopenia. Although sarcopenia can predict the prognosis in advanced cancer patients due to the catabolic process, it can be considered that it may be insufficient in predicting the prognosis in patients with PV and ET who have not yet developed a catabolic process. Cite this article as: Öztürk E, Gönen Ö, Erbakan A, Özünal IE. Evaluation of prognostic nutritional index and sarcopenia in polycythemia vera and essential thrombocythemia. Cerrahpaşa Med J. 2021;45(3):216-220.